Rancang Bangun Sistem Pakar Penyakit Hydrocephalus Berbasis Web - Sutedi, Ade; Baswardono, Wiyoga; Setiawan, Wawan (Jurnal Algoritma, 2025)
Hydrocephalus disease is a rare condition that generally occurs in children under 5 years old, although adults can also be affected. It is important to develop an expert system that can help diagnose, prevent and provide treatment solutions for this disease. This research uses the Expert System Development Life Cycle (ESDLC) methodology and forward chaining inference method, and conducts testing with Blackbox Testing. The result is an expert system that can diagnose early symptoms of hydrocephalus, offer prevention recommendations, and treatment solutions, thus helping patients detect this condition early and reducing costs and consultation time.